Body Acceptance, Body Dysmorphia Symptoms, and Selfie Behavior: Unpacking their Relationships Among Filipinos - Reyes, Marc Eric S.; Ang Tong, Alyssa Ashley O.; Cada, Sherry Lyn H.; Lopez, Raymond Nathan A.; Natividad, JV Louise D. (Makara Human Behavior Studies in Asia, 2025)
The emergence and proliferation of social media gave rise to “selfitis,” an obsession-compulsive engagement in photo selfie-related activities. This phenomenon raises a problem, especially for people experiencing body acceptance concerns and body dysmorphia symptoms, as both of these variables may be linked with photo selfie-taking behavior. With the Philippines having the second-highest average daily social media usage globally, this study explored the association between body acceptance, body dysmorphia symptoms, and selfie behavior. We utilized a cross-sectional explanatory design and investigated the possible mediating and moderating role of body dysmorphia symptoms in the relationship between body acceptance and selfies among 506 Filipinos aged 18–58 who voluntarily completed an online battery of tests measuring body acceptance, body dysmorphia symptoms, and selfie behavior. The results showed that body dysmorphia symptoms moderated and partially mediated the association between body acceptance and selfie behavior, offering a more in-depth understanding of these constructs among our Filipino sample. No clinical association was found between selfie-taking and body dysmorphia symptoms, challenging the notion that frequent selfie-taking is a direct symptom of body acceptance issues. Therefore, understanding and addressing body acceptance concerns requires us to move beyond one-size-fits-all approaches and always consider the specific cultural contexts in which they arise.